Isolated slow orthostatic tremor of the trunk - Aziz, N. Ahmad; Grobe-Einsler, Marcus; Kaut, Oliver (Neurological research and practice, 2022)
Slow orthostatic tremor is an extremely rare movement disorder with relatively low-frequency tremor (< 13 Hz) in the legs and trunk, which is evoked by standing. There is still much controversy regarding its precise etiology. Here we present a 57 year-old female patient with a slow orthostatic tremor variant who experienced progressive gait disturbances since six years due to isolated trunk tremor. Potential symptomatic causes of tremor and other neurological co-morbidities were excluded through an exenstive clinical, laboratoy and imaging work-up. Subsequently, a combined treatment with propranolol and primidone was started, which resulted in almost complete resolution of the trunk tremor. Given that the slow trunk tremor in this patient almost completely resolved after therapy with a low-dose propranolol and primidone, considered first line drugs for the treatment of essential tremor, this case illustrates that isolated orthostatic trunk tremor may occur as a rare variant of essential tremor.